An Unusual Cause of Cholestasis in an Infant: Biliary Atresia Type IIB - Sherwani, Poonam; Bolia, Rishi; Kaushik, Ashish; Kumar, Sumit; Kishore, Sanjeev; Chauhan, Udit (Indian Journal of Radiology and Imaging, 2021)
Biliary atresia (BA) is a progressive destructive cholangiopathy of unknown etiology that presents in early infancy. It has a worldwide frequency of 1:8,000–1:15,000 and is common in Asia than in the west. Based on the level at which the lumen of the extrahepatic duct is obliterated, BA is classified into three types. Type III is the commonest (∼85%) type and has the most proximal level of obstruction in the porta hepatis, while type II in which the atresia is at the level of the common hepatic duct, is the least common (∼2.5%) and has been rarely reported. Here, we report the imaging features of an infant with type IIB biliary atresia.
Keywords: biliary atresia; cholangiopathy; common hepatic duct